Angle Measurement Material Design Using Gymnastic Contexts for Pre-Service Elementary School Teacher - Lisnani, L; Suyono, Agus; Misdalina, M; Kesumawati, Nila (IndoMath: Indonesia Mathematics Education, 2023)
The purpose of this research is to produce a learning trajectory and analyze the angle measurement material using the context of gymnastic movements. The method used in this study is a design research method with the type of validation studies with the PMRI approach. The subjects in this study were pre-service elementary school teacher, totaling 6 people in the pilot experiment and 24 people in the teaching experiment. Data collection techniques using tests, observation and documentation. Data were analyzed descriptively on test results, observations and documentation obtained. The results of this study are in the form of material design and the results of an analysis of angle measurements using the context of gymnastics in the angle measurement material about angle sizes, angle shapes and types of angles form of a learning trajectory. Gymnastic movements are viewed from the movements of the hands, feet, limbs that form an angle.